2015
DOI: 10.3233/jad-150182
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cognitive Disorder: A Common Cause of Subjective Cognitive Symptoms

Abstract: Patients frequently present to the memory clinic with self-reported cognitive symptoms that cannot be attributed to structural, toxic, or metabolic causes, and are out of keeping with their performance on neuropsychological assessment. This can be considered to be Functional (psychosomatic) Cognitive Disorder, which results in significant patient distress and often has a major impact on social functioning and employment. We performed a retrospective analysis of the Bristol ReMemBr group cognitive clinic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 21 publications
2
35
0
2
Order By: Relevance
“…The observed frequency is higher than that reported in a retrospective database study from a memory clinic. 8 This study involved a single clinic over a limited time frame. Inevitably this will entail biases in the population studied (selection bias, referral bias), although no age criteria for referrals operate in this clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed frequency is higher than that reported in a retrospective database study from a memory clinic. 8 This study involved a single clinic over a limited time frame. Inevitably this will entail biases in the population studied (selection bias, referral bias), although no age criteria for referrals operate in this clinic.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective memory clinic database study diagnosed one third of patients presenting with cognitive complaints below the age of 60 years with FCD. 8 Previous experience in our dedicated cognitive disorders clinic based in a secondary care (neurosciences centre) setting has shown that more than 50% of patients referred are not diagnosed with dementia or mild cognitive impairment and that this has been a consistent observation over a number of years (Table 1, Figure 1). 9 It seems possible that many of these hitherto undiagnosed patients, previously labelled pragmatically in the clinic as having 'subjective memory complaint', may in fact qualify for a positive diagnosis of FCD as defined by Stone et al 7 We undertook a study with the following objectives: firstly to measure the frequency with which a diagnosis of FCD was made in patients attending a dedicated Functional cognitive disorders: memory clinic study Viraj Bharambe BM, BSc, MRCP, Andrew J Larner MD, PhD 'Functional cognitive disorders' (FCD) is a terminology suggested to denote patients who present with memory complaints but in whom no underlying cognitive disorder is found.…”
mentioning
confidence: 99%
“…[7]. Functional memory disorder was diagnosed twice as often in women as men and 9/19 patients were thought to have invalid neuropsychological results on the basis of effort testing.…”
Section: Studies Of Memory Clinicsmentioning
confidence: 99%
“…Alzheimer's disease (AD) is increasingly severe in this century . The clinical characteristics of AD are deficiencies in cognition . AD pathology is mainly characterized by excessive accumulation of toxic forms of amyloid‐β (Aβ), abnormally hyperphosphorylated tau and neurofibrillary tangles .…”
Section: Introductionmentioning
confidence: 99%